Forest management with variable retention impact over bryophyte communities of Nothofagus pumilio understory - Lencinas, María Vanessa (2008)
Bryophyte communities are an essential component of the understory in temperate forest, but few works analyze their potential as habitat indicators. Bryophytes, as the other plant species and wildlife, were significantly affected after the harvesting. For this, bryophyte cover, richness and biomass were compared in three different types and retention levels, and in unmanaged primary Nothofagus pumilio forest. A base line was determined prior to harvesting in a full site quality range and canopy gaps presence. Bryophyte communities were most abundant in low site quality class (13% cover and 844 kg.ha-1 biomass) than in high site quality class (5% cover and 357 kg.ha-1), while biomass differences were found inside the canopy gaps (1404 kg.ha-1). Silvicultural systems with different retention types significantly affect bryophytes after the harvesting. Most of the primary forest species decreased in the harvested sectors, as in the dispersed retention (15 to 30 m².ha-1) and clear-cuts, but the original bryophyte communities survive inside the aggregate retention. However, some life forms as tall turf growing better in the dispersed retention, while lax weft appears after the harvesting in the most open sectors (e.g. clear-cuts). The variable retention treatment, which combines the aggregated and the dispersed retention, appears as the most adequate forest management strategy in order to maintain the bryophyte biodiversity within a high conservation level.